A Logic Based Implementation of Head-Driven Phrase Structure Grammar - VOGEL, CARL; VOGEL, CARL (Elsevier, 1991)
Head-Driven Phrase Structure Grammar (HPSG), a unification-based formal language for describing linguistic phenomena, has a declarative semantics which makes it amenable to specification as a logic program. The HPSG formalism has undergone significant modification, becoming more declarative and incorporating greater lexicalization, since Proudian and Pollard first introduced a LISP-based HPSG chart parser in 1985. These theoretical developments have led us to the Prolog implementation of an HPSG interpreter which is described in this paper. We provide a brief introduction to the HPSG formalism, and then illustrate how a natural language grammar based on this formalism can be stated in a declarative notation that is directly interpretable by a Prolog chart-parser. This process leads us to refinements in both the specification of the formalism and the interpretation methodology.
Natural Language Understanding and Logic Programming, V.III
PUBLISHED
Amsterdam
Keywords: Computer Science; Ageing; Cancer; Creative Arts Practice; Creative Technologies; Digital Humanities; Inclusive Society; Intelligent Content & Communications; International Integration; Next Generation Medical Devices; Smart & Sustainable Planet; Telecommunications; Computational linguistics; SEMANTICS; SYNTAX; constraint-based grammar; head-driven phrase structure grammar; parsing